Mechanical and histological properties of native medial menisci compared to allograph medial menisci in the osteoarthritic knee - Weiske, Max; Riedel, Bianca; Kubosch, Eva Johanna; Mayr, Hermann O.; Schmal, Hagen; Seidenstuecker, Michael (Frontiers in Bioengineering and Biotechnology, 2024)
This study was designed to provide information on how the menisci change over the course of osteoarthritis, particularly with regard to their mechanical properties. The aim was to determine the difference between healthy menisci (fresh frozen meniscal transplants) and menisci harvested during total knee arthroplasty. The latter allows the grading of age-related and osteoarthritic changes in menisci on a macroscopic and microscopic level. Ten menisci from arthritic knee joints (medial) harvested during total knee arthroplasty were used and compared with 10 medial fresh frozen meniscal transplants. The mechanical measurements were carried out on a Mach-1 testing machine using indentation testing to determine the instantaneous modulus and the thickness of the menisci. The specimens were then embedded in paraffin, sectioned on a microtome and stained with hematoxylineosin and safranin-o. All measurements were divided into anterior horn, pars intermedia and posterior horn. There was no significant difference in the instantaneous modulus for the posterior horn in the fresh frozen menisci with 0.27 ± 0.1 MPa compared to the arthritic menisci with 0.18 ± 0.03 MPa. No significant difference could be determined for the meniscus thicknesses. There was a significant difference in the Safranin-O staining. There were also significant differences in the Pauli score: the arthrosis menisci showed a sum score that was on average 4 times higher than the sum score of the fresh frozen menisci.In the present study, it could be shown very well that there are significant differences in the mechanical properties as well as in the macroscopic and histopathological scores, such as the Pauli score used, between the fresh frozen meniscus allografts considered healthy and osteoarthritic menisci resulting from total knee arthroplasty. With a degradation score of 3 (Pauli), the instantaneous modulus was reduced by more than 50% compared to healthy controls. More importantly, however, the fresh frozen menisci only show a grade 2 when converting the sum values into grades -i.e. grade 2 means slight degeneration. This is interesting in that the fresh frozen meniscus transplants were always considered healthy in previous publications and should therefore actually have a grade 1.